Performance of durum wheat lines for quality and rust resistance - Oak, M D; Patil, R M; Bankar, D N; Bagwan, J H; Bipinraj, A L; Tamhankar, S A; Honrao, B K; Misra, S C (Journal of Cereal Research, 2011)
Stem rust (Puccinia graminis Pers. f. sp. tritici) and leaf rust(Puccinia triticina Rob. ex. Desm.) are the major constraintsin wheat production in the peninsular zone. A number ofwheat varieties cultivated in the past, became susceptibleto rust, after a few years of cultivation. Traditionally wheatimprovement aims at three major aspects viz. grain yield,disease resistance and quality. The effect of disease on yieldand its components in general has been adequately studied(Mundy 1973, Knott 1989). However, there is still amplescope to study its interaction with physiology and qualityin wheat. Allard (1960) suggested that early generationselection should be restricted to highly heritable traits suchas disease resistance and plant height and that the traitsshowing low heritability should be evaluated only in thoselines that survive this screening. Such a pedigree breedingsystem involves the retention of lines of unknown grain yieldpotential until a degree of homozygosity is attained (F5 orF6). In view of the severeness of the rust diseases, as well asthe necessity to improve the quality of wheat, an attempt hasbeen made to combine rust resistance and quality attributesin durum wheat.